Coronal Knee Malalignment in Young Adults and Its Link to Body Measures - Hershkovich, Oded; Thein, Ran; Gordon, Barak; Burstein, Gideon; Tenenbaum, Shay; Derazne, Estela; Tzur, Dorit; Afek, Arnon (The Journal of Knee Surgery, 2019)
Our aim was to report the prevalence of knee varus-valgus malalignment (KVVM) and its association with body mass index (BMI) and body height in a healthy and fit young adult population. Information on the disability codes associated with KVVM according to the Regulations of Medical Fitness Determination was retrieved from a medical database containing records of 17-year-old males and females before their recruitment into mandatory military service. Logistic regression models assessed the association between the BMI and body height to KVVM. The study cohort included 821,381 subjects (460,674 males and 360,707 females). The prevalence of KVVM was 0.9% in males and 0.6% for females. Under/overweight subjects were associated with higher prevalence of KVVM. The odds ratios (ORs) had a “J” curve pattern, increasing for underweight males and females, and even more so for above-normal BMIs (for obese males and for both overweight and obese females). The strongest association was between obese females and KVVM: an obese female had an OR of 22.864 (confidence interval [CI] = 20.683–25.725, p < 0.001) to have KVVM and an obese male had an OR of 4.483 (CI = 4.158–4.833 p < 0.001). When the BMI was analyzed as a continuous variable, each increase in one BMI unit was associated with an increase in OR of 7.6% for males and 24.1% for females. There is a strong association between BMI and KVVM in both underweight and overweight young adults. KVVM is more common in males, but most strongly associated with overweight and obese females.This is a Level III, case–control study.
Keywords: knee; malalignment; body mass index